Identification and Role of Microalgae Found in Catfish (Clarias gariepinus) Cultivation Pond - Zakiyyah Nur Inayah; Rahmat Ardi Kurniawan; Muhamad Fajar Aulia; Adif Pratama; R Adharyan Islamy (Nekton, 2025)
Microalgae play an essential role in aquaculture as primary producers, serving both as natural feed and as bioindicators for assessing pond water quality. The presence of specific microalgal taxa is crucial for evaluating aquatic conditions and identifying potential natural feed sources. This study aimed to identify microalgal species found in African catfish (Clarias gariepinus) culture ponds and to determine their ecological roles. A descriptive survey method was applied. Water samples were collected using a plankton net from three catfish culture ponds during August–September 2025. Identified microalgae were morphologically classified and analyzed for their potential as bioindicators based on literature review using Palmer’s Pollution Index. The results revealed 16 genera belonging to three divisions: Bacillariophyta (diatoms), Chlorophyta (green algae), and Cyanophyta (blue-green algae). Two genera of Bacillariophyta were identified—Aulacoseira and Synedra. Chlorophyta was the most dominant division, comprising 11 genera: Actinastrum, Coelastrum, Dictyosphaerium, Golenkinia, Micractinium, Oocystis, Pandorina, Pediastrum, Scenedesmus, Staurastrum, and Ulothrix. Cyanophyta included three genera—Anabaena, Aphanocapsa, and Spirulina. Among these, Scenedesmus and Pediastrum (Chlorophyta) are commonly used as natural feed, whereas Cyanophyta members are often utilized as water-quality bioindicators. The diversity and abundance of microalgae observed in the catfish ponds indicate organic enrichment, yet they also provide valuable potential as natural feed sources.